2021
DOI: 10.1172/jci.insight.146743
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to vaccine-preventable infections after CAR-T-cell therapy for B-cell malignancies

Abstract: In this prospective study, we investigated antibodies to vaccine-preventable infections and other pathogen-specific antibodies in individuals with remission after CAR-Tcell therapy for B-lineage malignancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(59 citation statements)
references
References 64 publications
0
50
0
Order By: Relevance
“…B-cell aplasia, plasma cell depletion, and resultant hypogammaglobulinemia are inevitable side effects of CD19/BCMA CAR T-cells and could predispose patients to infectious complications [55,56]. [57,58]. In conclusion, both patients and CAR T-associated factors lead to a cumulative immunosuppressive state, which predisposes CAR T-cell recipients to infections.…”
Section: Risk Factors Of Infectious Complications In Patients Receivi...mentioning
confidence: 99%
See 1 more Smart Citation
“…B-cell aplasia, plasma cell depletion, and resultant hypogammaglobulinemia are inevitable side effects of CD19/BCMA CAR T-cells and could predispose patients to infectious complications [55,56]. [57,58]. In conclusion, both patients and CAR T-associated factors lead to a cumulative immunosuppressive state, which predisposes CAR T-cell recipients to infections.…”
Section: Risk Factors Of Infectious Complications In Patients Receivi...mentioning
confidence: 99%
“…Lastly, BCMA-targeted CAR T-cells may also have more negative effect on post-CAR T pathogen-specific antibody level compared to CD19 CAR T-cell products [57]. Joshyula et al reported a cohort of 32R/R MM patients treated with BCMA CAR T-cell and observed that most patients had low IgG level and measles-specific IgG [33].…”
Section: Hematologic and Immune Recovery After Car T-cell Therapymentioning
confidence: 99%
“…This is consistent with Dahiya et al, which reported that antibody responses to common pathogens such as Epstein-Barr virus and in uenza were preserved despite their lower seroconversion rate against SARS-CoV-2 in CD19-directed CAR-T recepients. 13 Conversely, BCMA-targeting therapies eliminate mature plasma cells that are responsible for longterm immunity 35 . As such, while targeting BCMA may eliminate preexisting immunity from vaccinations before CAR-T therapy, it may be less disruptive to developing post-treatment immunity compared to CD19-directed treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Many patients maintain protective levels of vaccine-induced antibodies and against viruses, despite CD19 and serum IgG levels, 21 , 37 , 39 which appears to be associated with plasmocytes persistence following CD19+ lymphocytes depletion. Children with fewer plasmocytes can be more susceptible to infections than adults, 30 and these levels might be lower following anti-BCMA CAR-T. 40 Pathogens-specific IgG levels were similar for most pathogens in post-CAR-T cell therapy, with and without intravenous immunoglobulin replacement, except for S. pneumoniae . 40 Given these data, costs, and risks associated with intravenous immunoglobulin infusion, we do not recommend its use based solely on serum IgG levels.…”
Section: Management Of Car-t Cells Complicationsmentioning
confidence: 98%
“…Children with fewer plasmocytes can be more susceptible to infections than adults, 30 and these levels might be lower following anti-BCMA CAR-T. 40 Pathogens-specific IgG levels were similar for most pathogens in post-CAR-T cell therapy, with and without intravenous immunoglobulin replacement, except for S. pneumoniae . 40 Given these data, costs, and risks associated with intravenous immunoglobulin infusion, we do not recommend its use based solely on serum IgG levels. We suggest intravenous immunoglobulin replacement guided by clinical conditions (ex.…”
Section: Management Of Car-t Cells Complicationsmentioning
confidence: 98%